Applicability of clinical genetic testing for deep brain stimulation treatment in monogenic Parkinson’s disease and monogenic dystonia: a multidisciplinary team perspective - Rački, Valentino; Hero, Mario; Papić, Eliša; Rožmarić, Gloria; Čizmarević, Nada Starčević; Chudy, Darko; Peterlin, Borut; Vuletić, Vladimira (Frontiers in Neuroscience, 2023)
In this perspective article, we highlight the possible applicability of genetic testing in Parkinson's disease and dystonia patients treated with deep brain stimulation (DBS). DBS, a neuromodulatory technique employing electrical stimulation, has historically targeted motor symptoms in advanced PD and dystonia, yet its precise mechanisms remain elusive. Genetic insights have emerged as potential determinants of DBS efficacy. Known PD genes such as GBA, SNCA, LRRK2, and PRKN are most studied, even though further studies are required to make firm conclusions. Variable outcomes depending on genotype is present in genetic dystonia, as DYT-TOR1A, NBIA/DYTPANK2, DYT-SCGE and X-linked dystonia-parkinsonism have demonstrated promising outcomes following GPi-DBS, while varying outcomes have been documented in DYT-THAP1. We present two clinical vignettes that illustrate the applicability of genetics in clinical practice, with one PD patient with compound GBA mutations and one GNAL dystonia patient. Integrating genetic testing into clinical practice is pivotal, particularly with advancements in next-generation sequencing. However, there is a clear need for further research, especially in rarer monogenic forms. Our perspective is that applying genetics in PD and dystonia is possible today, and despite challenges, it has the potential to refine patient selection and enhance treatment outcomes.